2012
DOI: 10.1371/journal.pone.0040718
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Nutrition and the Prevalence of Thyroid Disease after Salt Iodization: A Cross-Sectional Survey in Shanghai, a Coastal Area in China

Abstract: BackgroundBoth insufficient and excess iodine may produce thyroid disease. After salt iodization in China, the median urine iodine concentration (UIC) of children aged 8–10 years appeared adequate. However, it is unknown whether dietary changes due to rapid economic development in Shanghai have affected whole population iodine nutrition.ObjectiveTo assess dietary iodine intake, UIC and the prevalence of thyroid disease in the general population of Shanghai.DesignA cross-sectional survey was conducted with gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
49
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 20 publications
8
49
3
Order By: Relevance
“…The intra-and interassay coefficients of variation (CV) were lower than 4.8% for the TSH values ranging from 0.008 to 150 mIU/L. The FT 4 , FT 3 , T 3 , T 4 , TPO-Ab and Tg-Ab mones. China initiated the program of Universal Salt Iodization (USI) in 1996, and most areas of the country have become iodine sufficient since the year of 2000 [5].…”
Section: Data and Sample Collectionmentioning
confidence: 92%
See 3 more Smart Citations
“…The intra-and interassay coefficients of variation (CV) were lower than 4.8% for the TSH values ranging from 0.008 to 150 mIU/L. The FT 4 , FT 3 , T 3 , T 4 , TPO-Ab and Tg-Ab mones. China initiated the program of Universal Salt Iodization (USI) in 1996, and most areas of the country have become iodine sufficient since the year of 2000 [5].…”
Section: Data and Sample Collectionmentioning
confidence: 92%
“…The corresponding normal levels of serum TSH, FT 4 , FT 3 , T 4 , T 3 , TPO-Ab and Tg-Ab provided by the manufacturers were 0.55-4.78 mIU/L, 11.5-22.7 pmol/L, 3.5-6.5 pmol/L, 58.1-140.6 mmol/L, 0.92-2.79 mmol/L, 0-60 U/mL and 0-60 U/mL, respectively.…”
Section: Clinical Characterization Of the Study Subjectsmentioning
confidence: 95%
See 2 more Smart Citations
“…28 Nonetheless dietary iodine intake remains insufficient among pregnant women in Shanghai, Zhejiang, and other coastal cities where iodine is considered sufficient for the general population. 29,30 A national survey from the Mainland reported that the median UIC levels of pregnant and lactating women were 123-224 μg/L and 109-224 μg/L, respectively; median UIC was higher among those in inland cities, because of a higher iodine level in the salt and greater household coverage. 31 In contrast, the progress in tackling iodine insufficiency in Hong Kong has been far from satisfactory.…”
Section: Discussionmentioning
confidence: 99%